The Principles of Energy Efficient Microclimate Provision in the Skyscraper “Biotecton” of 1 km Height (European Journal of Formal Sciences and Engineering, 2019)
The article deals with the formation of a healthy human living environment in superstructure buildings with the requirements of indoor air quality, environmental and constructive safety. The results of the development of "Biotecton" - an ultra-high-rise multi-functional building (the height is 1000 m) are presented. In order to effectively overcome the wind and seismic loads, the principles of the structure of the natural form (Gramineae stems, Triticale) are used. It is a multi-tiered spatial structure, in the nodes of which there are dampers for limiting oscillatory movements. For solving the problems of increasing the energy efficiency of ventilation and air conditioning, the use of air from height 1000 m with the minimum of anthropogenic pollution is investigated. Two mechanisms of the movement of air in a superstructure were investigated: natural impulses (under the action of gravitational pressure and wind) and mechanical (fans). It is shown that the natural pressure is insufficient for air movement. The mechanical impulse is necessary, but its energy requirement can be compensated by a renewable energy source - wind turbines with a total capacity of 5.3 MW. For high air quality, the use of "oxygen gardens" in green areas, which are evenly spaced along the entire height of the building, is explored. The study proposed a list of plants that effectively clean air from pollution, sequestrate excess CO2, enrich the air with oxygen and release phytoncides that effectively fight against pathogenic microorganisms.
Keywords: superstructure building, skyscraper, indoor air quality, ventilation, oxygen gardens